Non-timber forest products markets and potential degradation of the forest resource in Central Africa: the role of research in providing a balance between welfare improvement and forest conservation - Ndoye, O.; Ruíz Pérez, M.; Eyebe, A. (1999)
This paper investigates the importance of income generated from marketing selected NWFP in Central Africa., focuses on local markets in Cameroon and at the borders with the Central African Republic (CAR), equatorial Guinea and Gabon. The species considered are Irvingia spp. (bush mango nut), Cola acuminata (cola nut), Garcinia lucida (essock) and Garcinia kola (onie). The study found that the value of the NWFP marketed was US$753,000 in the first half of 1995 and US$499,000 in the same period of 1996. Of these amounts, the value of barks marketed (for both Garcinia lucida and Garcinia Cola) represented US$30,000 and US$23,500 in 1995 and 1996. The decline in the significance of NWFP marketed, as a result of lower supply, show thinnes of NWFP markets resulting from their dynamic and unpredictable nature, which changes the role of markets in assembling and distribution of NWFP from year to year. Future research should focus on determining the rate of bark harvest that would enable forest dweller to sustainably derive part of their livelihoods from Garcinia lucida and Garcinia kola while preserving these trees.